Unsuccessful treatment outcome and associated factors among smear-positive pulmonary tuberculosis patients in Kepong district, Kuala Lumpur, Malaysia - Fadly Syah Arsad; Noor Hassim Ismail (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this study was to assess tuberculosis (TB) treatment outcomes among new smear-positive pulmonary tuberculosis (PTB) patients and identify the risk factors of unsuccessful treatment outcomes in Kepong district, Kuala Lumpur, Malaysia. Design/methodology/approach - A retrospective cohort study was conducted using registry-based data from the Tuberculosis Information System (TBIS) between 2014 and 2018. Simple random sampling was used to select 734 males and 380 females from the TBIS registry. Smear-positive PTB patient's sociodemographic, clinical and behavioral characteristics were extracted and analyzed. Logistic regression was used to find the possible independent risk factors for unsuccessful treatment outcomes. Findings - The treatment success rate was 77.20% (n = 860) which was still below the target set by the WHO (>90%). In total, 254 patients showed an unsuccessful treatment outcome: 106 died, 99 defaulted, 47 not evaluated and 2 showed treatment failure. Unsuccessful treatment outcome was significantly associated with older age, male gender, non-citizen, unemployment and being HIV positive. Originality/value - The study focuses on all these contributing factors of unsuccessful treatment outcome for a better risk assessment and stratification of TB patients and identify effective surveillance and management strategies to strengthen the control programs of tuberculosis in Kepong district.